2021
DOI: 10.1186/s12974-021-02179-y
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 ablation enhances tolerance in heat stroke pathology by inhibiting IL-1β-mediated neuroinflammation

Abstract: Background Patients with prior illness are more vulnerable to heat stroke-induced injury, but the underlying mechanism is unknown. Recent studies suggested that NLRP3 inflammasome played an important role in the pathophysiology of heat stroke. Methods In this study, we used a classic animal heat stroke model. Prior infection was mimicked by using lipopolysaccharide (LPS) or lipoteichoic acid (LTA) injection before heat stroke (LPS/LTA 1 mg/kg). Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
10
0
3
Order By: Relevance
“…This activation results in the production of pro-inflammatory cytokines, e.g., IL-6, IL-1β, and tumor necrosis factor (TNF)-α ( 31 , 33 , 35 , 50 ). Moreover, the animal models of heat stroke have shown that, when LPS is present, NLRP3 (NOD-, LRR-, and pyrin domain-containing protein 3) inflammasomes are activated and drive neuroinflammation ( 81 ). A vicious cycle centered around intestinal injury ensues in heat stroke involving the release of nitric oxide, the leakage of gut-related endotoxins, and increased production of inflammatory cytokines (e.g., TNF-α, IL-1β, and IFN-γ) ( 35 ).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This activation results in the production of pro-inflammatory cytokines, e.g., IL-6, IL-1β, and tumor necrosis factor (TNF)-α ( 31 , 33 , 35 , 50 ). Moreover, the animal models of heat stroke have shown that, when LPS is present, NLRP3 (NOD-, LRR-, and pyrin domain-containing protein 3) inflammasomes are activated and drive neuroinflammation ( 81 ). A vicious cycle centered around intestinal injury ensues in heat stroke involving the release of nitric oxide, the leakage of gut-related endotoxins, and increased production of inflammatory cytokines (e.g., TNF-α, IL-1β, and IFN-γ) ( 35 ).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…Critically, normalization of the core temperature does not necessarily inhibit the systemic inflammatory response in heat stroke ( 1 ). Researchers have thus suggested and tried the modulation of the inflammatory response as a form of heat stroke treatment and prophylaxis, including with the administration of IL-1 receptor antagonists ( 81 , 84 ), corticosteroids ( 60 , 85 ), activated protein C ( 86 ), and the inhibition of nuclear factor-kB activity ( 1 ). Others have used oleoylethanolamide to inhibit LPS-induced TLR-4 stimulation of the immune response ( 50 , 87 ).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…Ішемія/реперфузія (І/R) призводить до значного зниження клітинного та мітохондріального дихання з подальшою активацією апоптозу клітин у тканинах кишечника навіть після 30-хвилинної неоклюзійної гіпотензії [25]. Більше того, поліморфноклітинні нейтрофіли самі по собі генерують реактивні кисневі метаболіти та безпосередньо взаємодіють з ендотеліальними клітинами судин, що призводить до мікроциркуляторних порушень у кишечнику, а незабаром і до втрати бар'єрної функції [33].…”
Section: науковий огляд / Scientific Reviewunclassified
“…The activation of P2X7R can promote the formation of NLRP3 inflammasome [ 16 , 17 ], which is an intracellular multimeric protein complex that initiates inflammatory response and cell death (pyroptosis and apoptosis) by activating its effector caspase-1 [ 18 20 ]. The active caspase-1 facilitates the production of proinflammatory cytokines IL-1β and IL-18 [ 21 23 ], and activates pyroptosis-related protein Gasdermin D (GSDMD) and apoptosis-related protein caspase-3 [ 24 – 26 ]. This may lead to gliosis, neuronal loss and white matter damage, consequently leading to cognitive impairment [ 27 ].…”
Section: Introductionmentioning
confidence: 99%